My friend Tommy [videorecording (DVD)] - Stankovic, Nem; Lee, Thomas (Freestyle Digital Media, 2023)
Tommy is a real-life 40-year-old virgin. He also still lives with his traditional Christian Korean parents under a curfew. He's never been on a date, kissed a girl, or cooked a meal, nor does he own a personal bank account. He's been suppressed and pampered his whole life, leaving him with almost no adult skills. For years, Tommy pleads with his unlikely best friend Nem, a 6'9 former pro basketball player turned comedian to "help him with the ladies". Nem agrees to take Tommy on a cross-continental quest for self-discovery. The two unlikely friends are joined by a group of young and unique comrades. They embark on a quest of challenges that will push Tommy out of his comfort zone and teach him lessons in attaining adulthood (from cooking to approaching women, dating, and even having sex). This trip will be a crash course in attaining the teens, 20s, and 30s that Tommy missed out on. As they travel, ideologies clash and past traumas are revealed.